Protecting Rice Grains in the Post-Genomic Era 2019
DOI: 10.5772/intechopen.85756
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Potential ofBacillus thuringiensis: An Overview

Abstract: The toxins of Bacillus thuringiensis (Bt) have shown great potential in the control of harmful insects affecting human health and agriculture, used as the main biological agent for the formulation of bioinsecticides due to its specificity to target different insects' orders. This has led Bt-based products to become the best-selling biological insecticides in the world since the genes encoding insecticidal proteins have been successfully used in novel insecticidal formulation, genetically engineered (GE) crops,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…Most of the effects are due to exposure to adverse temperature and continuous sunlight, which reduce the effectiveness of these products. 40 Several studies have demonstrated the negative effects on Bt performance after UV exposure, mainly leading to the loss of spore viability and toxin integrity and, consequently, to low insecticidal activity. 48 It is in this context that studies with the development of formulations have expanded, especially those analyzing encapsulation techniques.…”
Section: Encapsulation Strategies For Bmentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the effects are due to exposure to adverse temperature and continuous sunlight, which reduce the effectiveness of these products. 40 Several studies have demonstrated the negative effects on Bt performance after UV exposure, mainly leading to the loss of spore viability and toxin integrity and, consequently, to low insecticidal activity. 48 It is in this context that studies with the development of formulations have expanded, especially those analyzing encapsulation techniques.…”
Section: Encapsulation Strategies For Bmentioning
confidence: 99%
“…As described above, microbial agents, such as Bt, are susceptible to degradation when applied to the plant canopy. Most of the effects are due to exposure to adverse temperature and continuous sunlight, which reduce the effectiveness of these products . Several studies have demonstrated the negative effects on Bt performance after UV exposure, mainly leading to the loss of spore viability and toxin integrity and, consequently, to low insecticidal activity. …”
Section: Encapsulation Strategies For B Thuringiensismentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is difficult for the pathogen to attack those insects that feed inside the plant [32]. B. thuringiensis toxins have shown well-documented toxicity against various insects, including Lepidoptera, Diptera, Hemiptera, Coleoptera, and nematodes [35][36][37][38][39][40]. In cotton, B. thuringiensis has been widely reported as a biopesticide to control various insect pests [27,41,42].…”
Section: Bacillus Thuringiensismentioning
confidence: 99%